TMEM106B haplotypes have distinct gene expression patterns in aged brain - Yingxue Ren; Marka van Blitterswijk; Mariet Allen; Minerva M. Carrasquillo; Joseph S. Reddy; Xue Wang; Thomas G. Beach; Dennis W. Dickson; Nilüfer Ertekin-Taner; Yan W. Asmann; Rosa Rademakers (Molecular Neurodegeneration, 2018)
Abstract Background Single nucleotide polymorphisms (SNPs) inherited as one of two common haplotypes at the transmembrane protein 106B (TMEM106B) locus are associated with the risk of multiple neurodegenerative diseases, including frontotemporal lobar degeneration with pathological inclusions of TDP-43. Among the associated variants, rs3173615 (encoding p.T185S) is the only coding variant; however, non-coding variants may also contribute to disease risk. It has been reported that the risk haplotype is associated with higher levels of TMEM106B and increased levels of TMEM106B cause cytotoxicity; however, the precise mechanism through which TMEM106B haplotypes contribute to neurodegeneration is unclear. Methods We utilized RNA sequencing data derived from temporal cortex (TCX) and cerebellum (CER) from 312 North American Caucasian subjects neuropathologically diagnosed with Alzheimer’s disease, progressive supranuclear palsy, pathological aging or normal controls to analyze transcriptome signatures associated with the risk (TT) and protective (SS) TMEM106B haplotypes. In cohorts matched for disease phenotype, we used Analysis of Variance (ANOVA) to identify differentially expressed genes and Weighted Gene Co-expression Network Analysis (WGCNA) to identify gene networks associated with the risk and protective TMEM106B haplotypes. Results A total of 110 TCX and 116 CER samples were included in the analyses. When comparing TT to SS carriers, we detected 593 differentially expressed genes in TCX and 7 in CER. Gene co-expression network analyses further showed that in both TCX and CER the SS haplotype was positively correlated with gene networks involved in synaptic transmission, whereas the TT haplotype was positively correlated with gene networks enriched for immune response. Gene expression patterns of 5 cell-type-specific markers revealed significantly reduced expression of the neuronal marker and relative increases in all other cell markers in TT as compared to SS carriers in TCX with a similar but non-significant trend in CER. Conclusions By comparing the common TMEM106B risk and protective haplotypes we identified significant and partly conserved transcriptional differences across TCX and CER and striking changes in cell-type composition, especially in TCX. These findings illustrate the profound effect of TMEM106B haplotypes on brain health and highlight the importance to better understand TMEM106B’s function and dysfunction in the context of neurodegenerative diseases.